Metode Sorogan Dalam Pembelajaran Membaca Al-Qur’an di Pondok Pesantren - Chaerul Anwar (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2020)
This study aims to analyze the effectiveness of reading the Qur'an using the sorogan method at the Al-Falah Lulut Islamic Boarding School, Bogor. The method used is a deductive qualitative analysis research, with a case study at the Al-Falah Lulut Islamic Boarding School. Data collection is done by conducting interviews, observations, documentation, and literature review. The data analysis used is qualitative analysis. The results of the study show: The results of learning to read the Qur'an using the sorogan method for categories level one, two, and three are quite effective, in the processEven the children like learning, but the application of the sorogan method is largely determined by the abilities and skills of the tutor, because the sorogan system in teaching is the most difficult system of the entire Islamic education system.